APLIKASI IRIGASI TETES BERTINGKAT DENGAN TANAMAN CABE DI PERUMAHAN PADAT PENDUDUK KOTA MATARAM HULU - I Dewa Gede Jaya Negara; Bambang Harianto; Anid Supriyadi; Agus Suroso (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
This study aims to determine the ability of multilevel drip irrigation using a lateral pipe from a 12 mm Netafim (NTF) pipe and Â½" PVC on soil media in polybags with variations of soil to compost 70%: 30%, 50%: 50%, 30%: 70%. Tests were carried out with variations in the depth of the water tower 220 cm, 120 cm, and 30 cm from the lateral drip pipe to the irrigation uniformity (CU), irrigation distribution and irrigation depth produced. The research was conducted on a residential yard measuring 1.5 m x 4 m x 2 m, the distance between the network levels was 1m and the tower height was 2.5 m. The results showed that drip irrigation with PVC and NTF pipes resulted in a deviation of irrigation volume at each level of the network of about 2 ml, with a decrease in the deviation of irrigation volume from the deviation of drip irrigation with NTF-level pipes of about 85%. Tests on NTF drip irrigation with a soil composition of 70% at various tank volumes, obtained a maximum irrigation depth of about 13 cm-20 cm and a minimum irrigation depth of 30% soil ranging from 5 cm-14 cm. For the NTF and PVC drip irrigation tests, the highest irrigation depth was obtained on 30% soil with a maximum irrigation depth of 10 cm-15 cm, while the minimum irrigation depth was obtained on 70% soil ranging from 6cm to 10cm. The average uniformity of PVC pipe multilevel drip irrigation and NTF was obtained at 95% with a more even distribution of irrigation water volume at each level.